2016
DOI: 10.2196/resprot.6355
|View full text |Cite
|
Sign up to set email alerts
|

High Touch and High Tech (HT2) Proposal: Transforming Patient Engagement Throughout the Continuum of Care by Engaging Patients with Portal Technology at the Bedside

Abstract: BackgroundFor patients with complex care needs, engagement in disease management activities is critical. Chronic illnesses touch almost every person in the United States. The costs are real, personal, and pervasive. In response, patients often seek tools to help them manage their health. Patient portals, personal health records tethered to an electronic health record, show promise as tools that patients value and that can improve health. Although patient portals currently focus on the outpatient experience, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 61 publications
0
55
0
Order By: Relevance
“…While previous studies reported positive findings, including patient reports of enhanced engagement in the care process and satisfaction with care, none included patient-centered functionality such as the ability to send messages to the care team, allowing patients to input information or record noteselements that have been demonstrated to further enhance patients' engagement [10]. This is especially true with the proliferation of wearable devices, where data about an individual's health state can be collected by real-time sampling and analysis of a few parameters using noninvasive, inexpensive, and portable devices [26].…”
Section: Page 565mentioning
confidence: 98%
See 2 more Smart Citations
“…While previous studies reported positive findings, including patient reports of enhanced engagement in the care process and satisfaction with care, none included patient-centered functionality such as the ability to send messages to the care team, allowing patients to input information or record noteselements that have been demonstrated to further enhance patients' engagement [10]. This is especially true with the proliferation of wearable devices, where data about an individual's health state can be collected by real-time sampling and analysis of a few parameters using noninvasive, inexpensive, and portable devices [26].…”
Section: Page 565mentioning
confidence: 98%
“…Providing patients real-time access to health information has been demonstrated as a positive force for change in the way care is provided [10]. In this regard, Lu, et al [25] develop an App to inspect controlled substances in patient care units.…”
Section: Page 565mentioning
confidence: 99%
See 1 more Smart Citation
“…An IPP provides a hospitalized patient with similar functions to those found in outpatient portals, including the ability to view vital signs, laboratory results, medication information, schedule appointments and communicate with their provider. However, IPPs may offer additional functions such as meal planning, real-time messaging with the inpatient care team, daily schedules, and access to educational materials relevant to their specific conditions [11,12]. In practice, IPPs have been developed as websites and tablet apps, with hospitals providing the required technology as a component of care during the patient's stay.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first such implementations occurred in 2013 at The Ohio State University Wexner Medical Center (OSU) with Epic Systems' MyChart Bedside (MCB) product. As the first academic medical center to implement an IPP system-wide, OSU sought to use its unique position to document its journey and provide guidance on IPP adoption [11,12,16]. However, only recently has enough usage data been available upon which to explore outcomes through a "big data" approachspecifically through the analysis of audit log files.…”
Section: Introductionmentioning
confidence: 99%